Changes in height of jump of runners and untrained men during and after intermittent 100 dropping jumps every 20s - Mamkus, G.; Mickeviciene, D.; Streckis, V.; Skurvydas, A. (Education. Physical training. Sport, 2000)
The primary aim of the present study was to establish the difference, if any, and the causes of the difference in the changes of the height of jump of highly-skilled athletes, long-distance runners and sprinters (S), and untrained persons during and after intermittent 100 dropping jumps every 20 s. Healthy untrained (UT) men (n=12), well trained (members of the Lithuanian national team) track-and-field athletes, long-distance runners (LDR) (n=10) and track-and-field athletes-sprinters (S) (n=9), gave their informed consent to take part in all the experiments within the study. The first finding of our study is that after performing 100 dropping jumps with maximum intensity every 20 s all subjects demonstrated a significant decrease in the height of jumps performed in different ways and the height of jump was not restored even 24 hours after the end of the exercise; besides, the height of the jumps of sprinters performed using CMJ and DJ90 modes decreased to smaller extent if compared to the jumps performed by LDR and UT. The second finding of our study is that only in case of sprinters the change in the height of the jump after jumping exercise depended on the mode of the jump; besides, 30 min and 34 hours after the end of the jumping exercise the height of the jumps of sprinters performed using the CMJ and DJ90 modes decreased to a smaller degree than the height of the jumps performed using the SJ and DJ135 modes.